Herramientas digitales para el aprendizaje de la asignatura de Físico Química con los estudiantes de quinto semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología - Quishpe Quishpi, Carmen Teresa (2025)
The use of digital tools in the teaching of Physical Chemistry is essential in today's technological environment. These tools, such as ICT and TAC, are fundamental for facilitating the understanding of complex concepts. The research focused on proposing digital tools that contribute to learning in this discipline, with eXeLearning being the primary one. This study employed a quantitative approach with a non-experimental design and a descriptive scope, as it is both field-based and bibliographic in nature. The flipped classroom methodology was implemented to address topics such as Electricity, Magnetism, and Electrochemistry. For data collection, a digital survey with a Likert scale was used, applied to 21 students from the fifth semester of the Pedagogy of Experimental Sciences in Chemistry and Biology program. The results, after socializing the proposal, showed that the use of eXeLearning alongside other digital tools favors learning, presenting content through presentations, images, simulators, experimental guides, interactive videos, and educational games. This allows students to explore various topics in Physical Chemistry in a more dynamic way. The study concludes that digital tools, including eXeLearning, are valuable resources in the educational field, as they not only reinforce theoretical knowledge but also foster practical application and experimentation. Therefore, it is recommended to integrate digital tools into the learning of Physical Chemistry to improve students' understanding and interest in the subject.